Sub-chronic Toxicological Evaluation of Drinking Water from Internally Displaced Persons (IDP) Camp in Wassa, Federal Capital Territory, Abuja, Nigeria (Sahel Journal of Life Sciences FUDMA, 2024)
The number of Internally Displaced Persons (IDPs) camps has increased recently in Nigeria due to insurgency and natural disasters such as floods. This study aimed to evaluate the sub-chronic toxicological effects of the source of the drinking water in Wassa camp, Abuja, Nigeria. Forty-eight (48) mice were randomized into four (4) groups of twelve (12) mice each and orally administered different concentrations (5, 10, and 20 mL/kg body weight respectively) of the water sample from Wassa IDP for fourteen (14) days. The alteration was noticed in the liver and kidney indices of mice by a significant increase (p